2014
DOI: 10.1016/j.biomaterials.2013.12.066
|View full text |Cite
|
Sign up to set email alerts
|

NIR-light-induced surface-enhanced Raman scattering for detection and photothermal/photodynamic therapy of cancer cells using methylene blue-embedded gold nanorod@SiO2 nanocomposites

Abstract: Methylene blue-loaded gold nanorod@SiO2 (MB-GNR@SiO2) core@shell nanoparticles are synthesized for use in cancer imaging and photothermal/photodynamic dual therapy. For the preparation of GNR@SiO2 nanoparticles, we found that the silica coating rate of hexadecylcetyltrimethylammonium bromide (CTAB)-capped GNRs is much slower than that of PEGylated GNRs due to the densely coated CTAB bilayer. Encapsulated MB molecules have both monomer and dimer forms that result in an increase in the photosensitizing effect th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
122
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(124 citation statements)
references
References 39 publications
2
122
0
Order By: Relevance
“…In many reported studies, the intensity of the laser exceeded 1 W cm −2 , 8,[24][25][26] and it is only more recently that more attention has been paid to this parameter. 7,[27][28][29] Bimodal PTT and photodynamic cancer treatments are one way to overcome this limitation. 7 The development of novel gold nanostructures and hybrids with a more efficient light-to-heat conversion is the other option.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many reported studies, the intensity of the laser exceeded 1 W cm −2 , 8,[24][25][26] and it is only more recently that more attention has been paid to this parameter. 7,[27][28][29] Bimodal PTT and photodynamic cancer treatments are one way to overcome this limitation. 7 The development of novel gold nanostructures and hybrids with a more efficient light-to-heat conversion is the other option.…”
Section: Introductionmentioning
confidence: 99%
“…7 The development of novel gold nanostructures and hybrids with a more efficient light-to-heat conversion is the other option. 27,28,30 The wrapping and embedding of gold nanostructures within graphene oxide (GO) and reduced graphene oxide (rGO) could be a way into this direction. [31][32][33] Kohane and coworkers showed that rGO coated gold nanoparticles kill cells more rapidly under 808 nm irradiation with a laser intensity of 3 W cm −2 , than did uncoated particles.…”
Section: Introductionmentioning
confidence: 99%
“…AuNPs mediated PPT has been used widely as a preliminary treatment to melanoma, epithelial, breast and colon cancer cells both in vitro and in vivo. [31][32][33] Controlled surface engineering of AuNPs using ligands of tumor biomarkers and HIV Tat 49-57 which has a membrane translocation domain and a nuclear localization sequence have been successfully used to irreparably damage DNA of cancer cells via directly heating their nucleus through PPT. 34 In addition, noninvasive radiofrequency¯eld (RF,…”
Section: Aunps-based Tumor Contrast Imaging In Vivomentioning
confidence: 99%
“…Compared with conventional agents, NP-based imaging probes provide several advantages [40], including enhanced circulation halflife, the integration of "smart sensing" properties to the probes [41], and the ability to load both imaging and drug components in one vehicle for multifunctional applications [42]. Generally speaking, molecular imaging includes the use of optical techniques such as bioluminescence and fluorescence imaging [43], molecular magnetic resonance imaging (MRI) [44], magnetic resonance spectroscopy (MRS), positron emission tomography (PET) [45], single-photon emission computed tomography (SPECT) [46], and increasingly popular photoacoustic tomography (PAT) [40]. [12].…”
Section: Molecule Imagingmentioning
confidence: 99%